Molecular phylogeny of Acanthophyllum (Caryophyllaceae: Caryophylleae), with emphasis on infrageneric classification. Issue 3 (2nd June 2014) - Pirani, Atefeh; Zarre, Shahin; Pfeil, Bernard E.; Bertrand, Yann J.K.; Assadi, Mostafa; Oxelman, Bengt
Abstract: Despite being one of the larger genera of Caryophyllaceae with about 60 cushion‐forming subshrubby species, Acanthophyllum is represented poorly in previous molecular phylogenetic studies. The genus is an important component of the subalpine steppe flora in Central to Southwest Asia. Although the placement of Acanthophyllum in the tribe Caryophylleae and a close relationship to Allochrusa has already been suggested, the monophyly of the genus and its infrageneric taxa, as well as its relation to other closely related genera, have not been addressed. We have assembled datasets of nuclear ribosomal internal transcribed spacer (ITS) sequences and intron sequences of the chloroplast gene rps16 for 47 Acanthophyllum species and 63 species of 11 additional genera from Caryophylleae. Phylogenetic analyses were performed using maximum parsimony, maximum likelihood and Bayesian methods. Our analysis suggests that Allochrusa, Diaphanoptera, Ochotonophila and Scleranthopsis are nested within Acanthophyllum but that the traditionally recognized sections of Acanthophyllum are monophyletic after reassignment of a few species. Emarginate petals may be a synapomorphy for one of the two basal clades of Acanthophyllum . Moreover, non‐monophyly of the genera Gypsophila and Diaphanoptera is suggested by the present study. The age of the crown clade of Acanthophyllum s.l. is estimated to be 11.1 Ma by * BEAST species tree analysis.